Bioactivity of Piper aduncum L. essential oil for insect pests of stored products - Josiane Moura do Nascimento; Adalberto Hipólito de Sousa; Lucas Martins Lopes; Jamila Farias Mendonça; Ana Cláudia Vieira dos Santos (Pesquisa Agropecuária Tropical, 2023)
Determining the bioactivity of essential oils extracted from plants is crucial for the development of alternatives for controlling insect pests in stored grains. This study aimed to investigate the bioactivity of Piper aduncum L. essential oil for the control of Sitophilus zeamais (Coleoptera: Curculionidae), Sitophilus oryzae (Coleoptera: Curculionidae) and Cryptolestes ferrugineus (Coleoptera: Cucujidae). Bioassays were conducted to determine the oil toxicity, sublethal effects, attractiveness and flight initiation behavior. Toxicity tests were carried out to determine the lethal concentrations for 50 and 95 % of the insects (LC50 and LC95). Tests were also performed with sublethal exposures to C. ferrurineus, S. oryzae and S. zeamais, using their respective LC5 values (0.0002, 0.097 and 0.11 μL cm-2), to investigate effects on the attraction or repellency activity, as well as flight tests. C. ferrugineus showed greater LC50(0.0005 μL cm-2) and LC95 (0.0012 μL cm-2) susceptibility, in relation to S. oryzae LC50 (0.35 μL cm-2) and LC95 (1.26 μL cm-2), and S. zeamais LC50 (0.39 μL cm-2) and LC95 (1.40 μL cm-2). The exposure to the sublethal LC5 concentration influenced the behavioral responses of attractiveness/repellency and flight activity. The oil had a neutral effect on C. ferrugineusLC5 (0.0002 μL cm-2) and an attractive effect on S. oryzae and S. zeamais LC5 (0.097 and 0.11 μL cm-2), and can be considered a potential insecticide for controlling pest weevil species of stored grains.